Examining racial and gender biases in teaching evaluations of instructors by students on an online platform in the UAE - Lamba, Nishtha; Kishore, Sameer; Khokhlova, Olga (Frontiers in Education, 2023)
Introduction Student evaluations of teachers (SETs) carry significance for academics' career progression, but evidence suggests that these are influenced by students' expectations and biases. Previous research has shown that female lecturers are viewed less favorably compared to male lecturers. Racial bias has also been observed in higher education. For example, few studies administered in the U.S. found that African American lecturers received lower ratings than White lecturers. Current research investigates whether biases based on instructors' gender (male, female) and race (White and South Asian) influence university students' perception of instructors in an online teaching environment in the UAE. Methods Using a between group design, 318 participants viewed one of the four videos (male-South Asian, female-South Asian, male-White, female-White) of a virtual instructor teaching social psychology and then responded to teaching evaluation questions. Results Factorial ANOVAs were administered. Biases showcased consistent preference for male and South Asian lecturers. Male lecturers were perceived to be treating students with more respect, speaking in a more appropriate manner, displaying more enthusiasm for the subject, and more approachable than female lecturers. South Asian lecturers were perceived to be more sensitive toward students' feelings, displaying more enthusiasm for the subject, and more approachable than White lecturers. Overall, students expressed wanting to study more from male and South Asian lecturers compared to female and White lecturers. Discussion Biases emerged in interpersonal variables, such as approachability, sensitivity, enthusiasm for subject, and respect, and not in the domains of knowledge, presentation skills, and stimulating thinking. Findings reinforce that relying on teaching evaluations may not be accurate, and highlight how certain unconscious biases could impact professional growth of academics.